If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 9x + -5 = 4y + 1x + 3 Reorder the terms: -5 + 9x + 6y = 4y + 1x + 3 Reorder the terms: -5 + 9x + 6y = 3 + 1x + 4y Solving -5 + 9x + 6y = 3 + 1x + 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 9x + -1x + 6y = 3 + 1x + -1x + 4y Combine like terms: 9x + -1x = 8x -5 + 8x + 6y = 3 + 1x + -1x + 4y Combine like terms: 1x + -1x = 0 -5 + 8x + 6y = 3 + 0 + 4y -5 + 8x + 6y = 3 + 4y Add '5' to each side of the equation. -5 + 8x + 5 + 6y = 3 + 5 + 4y Reorder the terms: -5 + 5 + 8x + 6y = 3 + 5 + 4y Combine like terms: -5 + 5 = 0 0 + 8x + 6y = 3 + 5 + 4y 8x + 6y = 3 + 5 + 4y Combine like terms: 3 + 5 = 8 8x + 6y = 8 + 4y Add '-6y' to each side of the equation. 8x + 6y + -6y = 8 + 4y + -6y Combine like terms: 6y + -6y = 0 8x + 0 = 8 + 4y + -6y 8x = 8 + 4y + -6y Combine like terms: 4y + -6y = -2y 8x = 8 + -2y Divide each side by '8'. x = 1 + -0.25y Simplifying x = 1 + -0.25y
| 5+5*7+(7-5)^2/2 | | (8m^4n^6-12m^12n^-4)/(2m^12n^6) | | 5w+-90=3w | | -n/(-2p^0)^5 | | Ax^2-16a=0 | | y+6=10y-3 | | 6+5d=-4 | | (-27)/(-6-3) | | 64=6x-2 | | 3h-2(1+4h)= | | x-50=100 | | 9x+8=11+8x | | -16x=-80+4x | | (x-39)+x=475 | | 42+18= | | 3x-7=12x | | 85=4x-15 | | 4/5(m)=7 | | 6x^2-14x+4= | | 12=36-4x | | 2g+s=3r | | 5.2q-3.3-5.9q=1.7-4.6 | | -8(3-3x)=0 | | 5a-2=13 | | 11+11=1 | | 6x+-13=5x+-4 | | -4+r=8 | | (3x-10)+(x+8)=90 | | 5y+10x+12=27 | | ln*(2x+3)=ln*9 | | 5y-4=5+9y | | -2n-5n+16=0 |